Iridium(III)-catalyzed alkynylation of 2-(Hetero)arylquinazolin-4-one scaffolds via C-H bond activation - Rohokale, Rajendra S.; Kalshetti, Rupali G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
The directed C-H alkynylation of 2-(hetero)arylquinazolin-4-ones has been explored with the ethynylbenziodoxolone reagent TIPS-EBX employing an Ir(III) catalyst. Complementary conditions for either monoalkynylation or dialkynylation have been developed. Also demonstrated is the broad scope of this reaction and the compatibility of various functional groups such as -F, -Cl, -Br, -CF3, -OMe, -NO2, and alkyl, etc.